Mediating High-Stakes Global and Judicial Disputes - Aghenitei, Mihaela; Slabu, Elisabeta (Journal of Danubian Studies and Research, 2022)
What matters is the fact that mediation is a powerful possibility to cover human requirements, using a very fast, very effective but also relatively cheap solution to close the conflict. It raises the question of the existence of social justice which is closely related to the fact that mediation can bring individuals from a strong community to the same table. Mediation has the extraordinary ability to transform conflictual interaction into strengthening the relationship between the parties, including the society of which the parties are a part. However, we cannot deny the negative aspect of mediation, its harsh but also oppressive character that can increase the power of a state over individuals, respectively of the strong over the weak. The timely resolution of the conflict is the main beneficial effect of mediation as an inexpensive and fast alternative to the legal process, but it thus denies the right of the poor parties to compensation, to the legislation on the protection of human rights, although speed is guaranteed. The purpose of deepening the notion of mediation is to show its potential both from a legal point of view and in society, in the resolution of minor, traditional conflicts.